Upaya Meningkatkan Kemampuan Membaca Anak Usia 5-6 Tahun Menggunakan Media Tulisan Pada Bungkus Makanan Ringan di TK Aisyiyah Bustanul Athfal II Bangkinang Kota - Marliyana Marliyana; Musnar Indra; Vitri Anggraini (Jurnal Pendidikan Tuntas, 2025)
This study aims to improve the early reading skills of 5- to 6-year-old children at Aisyiyah Bustanul Athfal II Kindergarten in Bangkinang City through the use of written text on snack packaging. The main issues identified were the children’s limited ability to recognize letter shapes and sounds, as well as their lack of interest in conventional learning materials. This study is a Classroom Action Research (CAR) conducted in two cycles. The research subjects consisted of 19 children in Group B. The results showed a significant improvement: in the pre-intervention phase, the classical achievement rate was only 16%–63% (Not Yet Developed category). After the intervention in Cycle I, the children’s skills began to improve but were not yet optimal. In Cycle II, the success rate reached 94.73%, with 17 children in the Very Well Developed (VWD) category. The conclusion of this study is that the use of text-based media on snack food packaging effectively improves children’s early reading skills through visually appealing stimuli that are familiar to their daily lives.